Informational literacy in higher education: design of a mensuration tool - María del Carmen Toledo Sánchez; Sonia Elizabeth Maldonado-Radillo (Biblios, 2015)
Objective. To show psychometric research phase to examine the validity of an instrument designed to measure information literacy in the Institutions of higher education in Mexico. Method. The questionnaire design of 50 items was based on the UNESCO standards of information and communication technologies (ICT) competencies for teachers and skills standards for access and use of information in higher education. The methodological strategy contemplated verification of content validity, item-item correlation and construct through factorial analysis. The sample was 73 professors and librarians who work in educational institutions of northwestern Mexico. Results. The final design was reduced to 44 items, and it demonstrated the items evaluate the same construct in their internal structure, and revealed 5 dimensions for informational variable competencies and 5 competencies for ICT. Conclusions. The items have good clarity regarding the specific concept, nevertheless, the elimination of 6 items was needed proving to be a valid and reliable instrument to measure the informational literacy in the studied context.